An Overview of Epigenetic Methylation in Pancreatic Cancer Progression - Zhao, Yuhao; Yang, Mao; Wang, Shijia; Abbas, Sk Jahir; Zhang, Junzhe; Li, Yongsheng; Shao, Rong; Liu, Yingbin (Frontiers in Oncology, 2022)
Over the past decades, the aberrant epigenetic modification, apart from genetic alteration, has emerged as dispensable events mediating the transformation of pancreatic cancer (PC). However, the understanding of molecular mechanisms of methylation modifications, the most abundant epigenetic modifications, remains superficial. In this review, we focused on the mechanistic insights of DNA, histone, and RNA methylation that regulate the progression of PC. The methylation regulators including writer, eraser and reader participate in the modification of gene expression associated with cell proliferation, invasion and apoptosis. Some of recent clinical trials on methylation drug targeting were also discussed. Understanding the novel regulatory mechanisms in the methylation modification may offer alternative opportunities to improve therapeutic efficacy to fight against this dismal disease.